Light from old times - Ryle, John Charles, 1816-1900 (Welwyn, UK Evangelical Press, 1980)
Includes bibliographical references.
Reprint. Papers on Hooper and Latimer first published 1868 and then other papers in a volume entitled Light from Old Times, first published 1890. See also "Five English reformers" by J.C. Ryle
Donated by David Marshall, October, 1981.
Keywords: Hooper, John, -- 1495-1555; Taylor, Rowland, -- d.1555; Latimer, Hugh, -- c.1485-1555; Bradford, John, -- c.1520-1555; Ridley, Nicholas, -- c.1500-1555; Wycliffe, John, -- c.1329-1384; Rogers, John, -- c.1500-1555; Ward, Samuel, -- 1577-1639; Laud, William, -- 1573-1645; Baxter, Richard, -- 1615-1691; Gurnall, William, -- 1616-1679; Reformation -- England -- Biography